2009
DOI: 10.1016/j.bpj.2008.12.1836
|View full text |Cite
|
Sign up to set email alerts
|

Energetics Of Peptide (pHLIP) Binding To And Folding Across A Lipid Bilayer Membrane

Abstract: Andreev, O. A., Segala, M., Markin, V. S., & Engelman, D. M. (2008).Energetics of peptide (pHLIP) binding to and folding across a lipid bilayer membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
3
22
0
Order By: Relevance
“…However, it is of note that the lipid to peptide ratio used in the NMR experiments was 75:1, whereas our simulations were conducted at a ratio of 200:1. Previous studies have shown that binding of pHLIP is affected by lower lipid:peptide ratios, leading to a "parking problem" for pHLIP on the bilayer surface (9). For the orientations that remained bound to POPC, the 0 • , 72 • , and 288 • orientations all had distance distributions for A27 that were > 10 Å in agreement with the NMR experiments.…”
Section: Partitioning Of Phlip Influenced By Location Of Acidic Residuessupporting
confidence: 79%
See 1 more Smart Citation
“…However, it is of note that the lipid to peptide ratio used in the NMR experiments was 75:1, whereas our simulations were conducted at a ratio of 200:1. Previous studies have shown that binding of pHLIP is affected by lower lipid:peptide ratios, leading to a "parking problem" for pHLIP on the bilayer surface (9). For the orientations that remained bound to POPC, the 0 • , 72 • , and 288 • orientations all had distance distributions for A27 that were > 10 Å in agreement with the NMR experiments.…”
Section: Partitioning Of Phlip Influenced By Location Of Acidic Residuessupporting
confidence: 79%
“…Peptide insertion is induced by a shift from alkaline to acidic pH, with an apparent pK of insertion in 1-palmitoyl-2-oleoyl-snglycero-3-phosphocholine (POPC) membranes of ∼6.1 (9). This shift in pH spurs the protonation of two acidic residues (D14 and D25) in the membrane-spanning region of the peptide, leading to an increase in hydrophobicity and triggering the folding and insertion of the peptide across the lipid bilayer (9,10). The presence of two tryptophan residues (W9 and W15) allow intrinsic fluorescence spectroscopy to be used to detect the transition of pHLIP from state I → II → III.…”
Section: Introductionmentioning
confidence: 99%
“…Other organic solvents frequently utilized for studying TM peptides include dimethyl sulfoxide (DMSO), methanol, ethanol, 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP), and other hydrogenated or halogenated alcohols as well as mixtures of the above. A few TM peptides are also soluble in water and aqueous solutions, which is of great value for the quantitative description of spontaneous membrane insertion (Hunt et al, 1997b;Wimley and White, 2000;Reshetnyak et al, 2008; see also Sections 4.2 and 6.2) or hydrophobic partition equilibria (see Section 4.3).…”
Section: Isotropic Solventsmentioning
confidence: 99%
“…LN pHe can be probed using pH indicators injected into either the tail vein or footpad (Fig S4A). The pH Low Insertion Peptide, pHLIP ® (21,22), conjugated to an 800 nm-emitting fluorescent dye (IR800), was injected into the footpad (40-60 µl of 40 µM), and LNs were harvested 24 hr later for ex vivo imaging.…”
Section: Fig 2f) Indicating a Lactate Transport Is A Protein (Mct) mentioning
confidence: 99%